2016
DOI: 10.1111/jonm.12374
|View full text |Cite
|
Sign up to set email alerts
|

The organisational silence of midwives and nurses: reasons and results

Abstract: Activities that raise the awareness of hospital administrations and employees about preventing the factors that cause and maintain silence in hospitals should be planned.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
53
2
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(60 citation statements)
references
References 11 publications
4
53
2
1
Order By: Relevance
“…Comparing with others studies, these scores were higher than Yalçın and Baykal's () study and lower then Yurdakul et al. 's () study. Yurdakul et al.…”
Section: Discussioncontrasting
confidence: 67%
See 2 more Smart Citations
“…Comparing with others studies, these scores were higher than Yalçın and Baykal's () study and lower then Yurdakul et al. 's () study. Yurdakul et al.…”
Section: Discussioncontrasting
confidence: 67%
“…Social factors include a climate of mistrust and obedience to group behaviours. Finally, organisational factors include the coding of certain issues as taboo, not discussing issues that may be defined as taboo and an emphasis on manager–employee relationships (Donaghey, Cullinane, Dundon, & Wilkinson, ; Yurdakul, Aydın Beşen, & Erdoğan, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…One study on communication and silent behavior among operating room nurses and surgeons determined that nurses did not share their knowledge deficiencies with doctors, despite being members of the same multi‐disciplinary team (Gardezi et al, ). Nurses, especially, tend to remain silent concerning ethical and administrational issues (Çaylak & Altuntaş, ; Yalçın & Baykal, ; Yurdakul, Beşen, & Erdoğan, ). However, another study conducted with 601 doctors and nurses indicated that both remained silent concerning administrational issues that might affect patient safety (Harmanci et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…In a study about silence, midwives and, nurses stated that there was more silence on ethical issues and responsibility [42]. Therefore, it is critical to address and prevent it [43]. Silence as a Consequence of DBs was also in line with the findings of Chrouser and Partin 2019 [6].…”
Section: Deviated Focus From Patients To the Surgeonmentioning
confidence: 59%